2017
DOI: 10.1021/acs.jpclett.7b02601
|View full text |Cite
|
Sign up to set email alerts
|

New Insight into the Origin of the Red/Near-Infrared Intense Fluorescence of a Crystalline 2-Hydroxychalcone Derivative: A Comprehensive Picture from the Excited-State Femtosecond Dynamics

Abstract: Fluorescence upconversion and transient absorption techniques are used to explain the source of the intense red/near-infrared emission of crystalline 4-dimethylamino-2'-hydroxychalcone. We found that the initially excited enol form undergoes tautomerization in 3 ps to form the keto tautomer. The latter is stable in the ground state as a consequence of J-type aggregation in the crystal packing and is manifested in an absorption peak at 550 nm that spectrally overlaps with the short-lived enol emission, leading … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
50
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(58 citation statements)
references
References 23 publications
8
50
0
Order By: Relevance
“…The experimental absorption in the solid state shows two bands which have previously been attributed to absorption from the E and K forms. 43,72 Our calculations show that ), fast absorption from K forms generated in the excited state could be also possible. The dynamic nature of these processes is in line with the broad structure of the low energy band.…”
Section: Point Charge Embedding: Electrostatic Effects In the Crystalmentioning
confidence: 74%
“…The experimental absorption in the solid state shows two bands which have previously been attributed to absorption from the E and K forms. 43,72 Our calculations show that ), fast absorption from K forms generated in the excited state could be also possible. The dynamic nature of these processes is in line with the broad structure of the low energy band.…”
Section: Point Charge Embedding: Electrostatic Effects In the Crystalmentioning
confidence: 74%
“…An illustrative example is a derivative of 2′‐hydroxychalcone (HC), which upon the addition of a methoxy group in para position with respect to the hydroxyl group turns off its emissive character in crystal form, bringing the fluorescence quantum yield from 0.32 to less than 0.01 . The new molecule is (E)‐1‐(2‐hydroxy‐5‐methoxyphenyl)‐3‐(4[dimethylamino]phenyl)prop‐2‐en‐1‐one (DAP).…”
Section: Featuresmentioning
confidence: 99%
“…The optimization of excited state geometries in detailed condensed phase environments has numerous applications. For instance, the fluorescence of HC (see Section 3.1.1) can also be switched off by the substitution of a methyl group in para position with respect to the hydroxyl group, resulting in another dark compound: (2E)‐3‐[4‐(dimethylamino)phenyl]‐1(2‐hydroxy‐5‐methylphenyl)‐2‐propen‐1‐one (DMAP) …”
Section: Featuresmentioning
confidence: 99%
“…An illustrative example is a derivative of 2'-hydroxychalcone (HC), which upon the addition of a methoxy group in para position with respect to the hydroxyl group turns off its emissive character in crystal form, bringing the fluorescence quantum yield from 0.32 to less than 0.01. 24,25 The new molecule is (E)-1-(2,5-dimethoxyphenyl)-3-(4-(dimethylamino)phenyl)prop-2-en-1-one (DAP). While HC exhibits herringbone style packing, DAP has a complex unit cell structure whose steric constraints on the individual molecules are unclear at first glance.…”
Section: Dependenciesmentioning
confidence: 99%
“…For instance, the fluorescence of HC (see section 2.1.1) can also be switched off by the substitution of a of a methyl group in para position with respect to the hydroxyl group, resulting in another dark compound: (2E)-3-[4-(Dimethylamino)phenyl]-1-(2-hydroxy-5-methylphenyl)-2-propen-1-one (DMAP). 24,25 Both HC and DMAP can experience excited state intramolecular proton transfer, splitting the excited state into two potential decay pathways. It was recently computationally shown that in HC, both the enol and the keto non-radiative decay pathways were rendered energetically inaccessible by a combination of molecular and crystalline factors.…”
Section: Example Of Usementioning
confidence: 99%